A study on the employment outlooks of Chinese university students majoring in Japanese: A government recruitment perspective - Zhang, Ziran; Hasan, Ahmad (Global Academic Excellence (GAE), 2024)
This study explores the employment outlooks of Chinese university students majoring in Japanese and their potential career development within government sectors from the viewpoint of government recruiters. Through semi-structured interviews with ten recruitment personnel from the Ministry of Foreign Affairs of China, we analyze their evaluations of the abilities of Japanese major graduates and the key factors influencing hiring decisions. The research finds that, although Japanese major students generally possess strong language skills, they exhibit gaps in cross-cultural adaptability, career planning awareness, and integrated competencies compared to the actual demands of government departments. Recruiters emphasize the necessity for Japanese major students to have a background in international affairs and stronger overall qualities to tackle the complexities and challenges of diplomatic work. Based on the findings, this paper offers relevant policy recommendations: universities should adjust the curriculum for Japanese majors, increase interdisciplinary course offerings, enhance career planning guidance, and establish collaboration mechanisms with government departments to provide students with more internship and practical opportunities. These measures aim to improve students' overall competitiveness and better meet the government’s need for versatile foreign language talents. Future research could further explore the differing demands for foreign language talents across various types of government departments to optimize the direction of foreign language education and policy-making.